Model-driven development for pervasive information systems - Fernandes, José Eduardo (2012)
This chapter focuses on design methodologies for pervasive information systems (PIS). It aims to contribute to the efficiency and effectiveness of software development of ubiquitous services/applications supported on pervasive information systems. Pervasive information systems are comprised of conveniently orchestrated embedded or mobile computing devices that offer innovative ways to support existing and new business models. Those systems are characterized as having a potentially large number of interactive heterogeneous embedded/mobile computing devices that collect, process, and communicate information. Also, they are the target of technological innovations. Therefore, changes in requirements or in technology require frequent modifications of software at device and system levels. Software design and evolution for those require suitable approaches that consider such demands and characteristics of pervasive information systems. Model-driven development approaches (which essentially centre the focus of development on models, and involve concepts such as Platform-Independent Models, Platform-Specific Models, model transformations, and use of established standards) currently in research at academic and industrial arenas in the design of large systems, offer potential benefits that can be applied to the design and evolution of these pervasive information systems. In this chapter, we raise issues and propose strategies related to the software development of PIS using a model-driven development perspective.